DIAGNOSIS INFEKSI SITOMEGALOVIRUS PADA BAYI DAN ANAK - Rampengan, Novi H. (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: The prevalence of cytomegaloviral (CMV) infection is still high in developing countries, including Indonesia. CMV often causes intra-uterine infection with an incidence of 7 per 1,000 live births. Around 12.7% of babies with CMV infection develop symptoms since birth and around 13.5% of babies without any symptom develop sequel, including disruption of sensorineural hearing when the children age. CMV can be diagnosed with a single or combined examination by using amniocentesis, virus culture, PCR, antigenemia plus serologic IgM and IgG CMV, however, it is important to understand when these examinations will be performed and to evaluate the interpretation.Keywords: CMV, diagnosis, single examination, combined examinationAbstrak: Prevalensi infeksi sitomegalovirus (CMV) masih tinggi di negara berkembang, termasuk Indonesia. CMV sering dapat menyebabkan infeksi intra-uterin dengan insidensi 7 per 1000 kelahiran hidup. Sebanyak 12,7% bayi yang terinfeksi CMV memperlihatkan gejala saat lahir dan sebanyak 13,5% bayi yang tidak memperlihatkan gejala berkembang menjadi sekuele termasuk di dalamnya gangguan pendengaran sensorineural saat anak-anak. Diagnosis CMV dapat dilakukan dengan pemeriksaan tunggal maupun kombinasi menggunakan amniosintesis, kultur virus, PCR, antigenemia serta serologi IgM dan IgG CMV, namun penting untuk mengetahui saat dilakukan pemeriksaan tersebut dan bagaimana interpretasinya.Kata kunci: CMV, diagnosis, pemeriksaan tunggal, pemeriksaan kombinasi